There's gonna be some trouble : the five year Rooseum book 2001-2006. - Stenbeck, Katarina; Alves, Lennart; Büchler, Pavel; Carpenter, Ele; Crone Jensen, Lene; Dahlberg, Isabell; Esche, Charles; Ferré, Rosa; Gillberg, Frans; Gussin, Graham; Keller, Christoph; Lunghi, Enrico; et al. (Malmö : Rooseum - Center for Contemporary Art, 2007)
Ader, Bas Jan ; Althamer, Pawel ; Amtoft, Andre ; Antonijevic, Dejan ; Armleder, John M. ; Ask, Kristina ; Auder, Michael ; AUPG ; Bain, Mark ; Banner, Fiona ; Bartana, Yael ; Berkenbosch, Caroline ; Billgren, Ola ; Billing, Johanna ; Bismuth, Pierre ; Blum, Michael ; Bode, Mike ; Böttcher, Ann ; Bradley, Will ; Bustnes, Maria ; Casinière, Joëlle de la ; Creed, Martin ; Dumas, Marlene ; Durakovic, Nermin ; Einarsson, Gardar Eide ; Eriksson, Annika ; Ersen, Esra ; Fastland/Ground ; Ferri, Jakup ; Franszon, Gudni ; Frei, Luca ; Future Archive ; Gerber, Alison ; Geyer, Andrea ; Gillick, Liam ; Gordon, Douglas ; Gussin, Graham ; Hasselberg, Per ; Hayes, Sharon ; Heimerdinger, Isabell ; Holm Hvilsby, Soren ; Horelli, Laura ; Huyghe, Pierre ; IRWIN ; Johannesson, Sture ; Kameric, Sejla ; KesselsKramer ; Kogo, Takuji ; Kolding, Jakob ; Korpys, Andree & Markus Löffler ; Kusama Yayoi ; Kusolwong Surasi ; Lederlin, Jacques ; Leiderstam, Matts ; Lewis, Mark ; Lindberg, Maria ; Loevendie, Theo ; Lowenstein, Lyn ; van Manen, Hans ; Matt, Jung von ; McCail, Chad ; van Meene, Hellen ; Michaelsen, Jorgen ; Mik, Aernout ; Monk, Jonathan ; Moshri, Farhad ; Müller, Claudia & Julia ; Nelson, Mike ; NEW ; Numan, Toek ; Nyberg, Lisa ; Ögüt, Ahmet ; Olsson, Olof ; Ostojic, Tanja ; Özgen, Erkan ; Ozkaya, Serkan ; Penalva, João ; Perjovschi, Dan ; Pol, Bik Van der ; Rist, Pipilotti ; Roth, Dieter ; S,C,P,F... ; Saatchi & Saatchi ; Sakamoto, Ryuichi ; Salmi, Piia ; Samadian, Seifollah ; Sander, Katya ; Sasnal, Wilhelm ; Schmidt, Staffan ; Schmidt-Bleek, Cornelia ; Shahbazi, Setarah ; Shahbazi, Solmaz ; Sköld, Nilsmagnus ; Skov, Pernille ; Solakov, Nedko ; Sonjasdottir, Asa ; Stampes, Karl ; Stark, Frances ; Steamboat Switzerland ; Stevenson, Michael ; etc.
boek
Keywords: Zweden